Pemanfaatan open access Jurnal Borneo Administrator melalui pengukuran kepuasan pembaca di Lembaga Administrasi Negara - Dewi Sartika; Ricky Noor Permadi (Universitas Padjadjaran, 2020)
Open Access Journal (OAJ) is a journal publication that contains articles in full text and user’s can be accessed and used free of charge. The purpose of this study was to determine the extent to which open access was used in the Borneo Administrator Journal (JBA) by measuring reader satisfaction. The research method used was a descriptive quantitative approach. The data collection used a survey method and a data analysis technique used a simple descriptive statistical method. This research has eight research questions, namely the level of user’s satisfaction with access and download facilities, Kemenristek/Dikti accreditation, language, benefit for the profession and career advancement, number of articles and columns, overall format and content, issued quarterly (3x a year), and services provided by JBA managers. The research data analysis has the three highest indicators were published every quarter (3x a year), the format and content as a whole, and were beneficial for professional and career advancement. The lowest score indicators but still in the satisfied category were download facilities, language, and the number of articles and columns. In conclusion, the overall level of reader satisfaction is in the satisfied category. The implementation of open access in the Borneo Administrator Journal is basically to support the development and dissemination of knowledge.